The Influence of Health Education, Health Services, and Environmental Development of School Health on Adolescent Reproductive Health Behavior - Amenda Paswida Sebayang; Rosalina Br Sitepu; Muhammad Mujtaba Asad; Astriana Fransiska Butarbutar; Fery Arjuna Sembiring (Universitas STRADA Indonesia, 2025)
Background: Teenage problems are increasing every year, starting from teenage fights, using drugs, consuming alcohol, smoking, and even cases of teenage pregnancy. Globally, the condition of health problems in adolescents is alarming. This is triggered by bad teenage behavior. This behavior can, among other things, reduce self-control and increase risky behavior such as engaging in casual sex which can result in unwanted pregnancies. School health unit or in Indonesian called UKS is expected to become a forum for improving students' abilities and skills in developing healthy living behavior. Purpose: The research aims to analyze the influence of school health services on adolescent reproductive health behavior. Methods: The research method was quantitative with a cross-sectional design. The population was 72 teenagers by total sampling. Data analysis used chi-square and multiple logistic regression. Results: The results showed statistical test comparison between Reproductive Health Behavior and Health Education, Health Services, and Environmental Development, respectively shows p-value = 0.014 (p< 0.05), 0.010 (p< 0.05), and 0.046 ( p < 0.05) which means Ha is accepted or there is a correlation between adolescent reproductive health behavior and health education, health services, and environmental development. The independent variable that influences reproductive health behavior has a value of 0.041 or <0.05. The multiple logistic regression test show that the health service variable has an Exp (B) value of 2.917. Conclusion: In conclusion, the adolescent reproductive health education, UKS health services, and environmental development have a 2.917 chance of influencing adolescent reproductive health behavior. In other words, there is significant influence of UKS health services on adolescent reproductive behavior.